The Antiradical Activity of Insoluble Water Suji (Pleomele angustifolia N.E. Brown) Leaf Extract and Its Application as Natural Colorant in Bread product - Jokopriyambodo, Wahyu (Fakultas Farmasi, Universitas Gadjah Mada, 2014)
Currently, there are some synthetic colouring agents present in food products. The synthetic colouring agents are supposed to give deleterious effect to human health; therefore, natural coloring agents derived from plant is continuously explored to replace the synthetic ones. Suji (Pleomele angustifolia) leaf is one of the potential plant to be used as natural coloring agents. The aim of this study is to explore the natural colour potency and antiradical activity of insoluble water extract of suji leaf from three different regions. Furthermore, green components obtained from suji leaf extract (SLE) was used for coloring food product (bread product), and bread added with extract was subjected to preference test, namely color and taste preferences by trained panelist. The result showed that region and maturity level affect the intensity of green components obtained from SLE. The highest level of green components (2.57 %) among three regions evaluated was observed from Jumantono. The water insoluble extract of suji leaf can also make coloring effects toward bread and exhibits low radical scavenging against 2,2-diphenyl-1-picrylhidrazyl. The preference test against color and taste of bread added with synthetic coloring agents and mixed with SLE showed that the coloured bread is less preferred than that without coloring agent.